Study of Takhrij and Understanding of Hadith Regarding The Implementation of Prayer in Marabidh Al-Ghanam - Indah Rahmania; Muhammad Taufik (International Journal of Research, 2024)
In terms of performing prayers, there are traditions that state the permissibility of praying in marabidh al-ghanam (goat sheds) but prohibit praying in camel sheds. The goat pen itself is a place that is synonymous with dirt and unclean. While in the implementation of prayer we are required to maintain the sanctity of clothing and places of worship from dirt and unclean. The purpose of this study is to determine the quality and understanding of the Hadith of the Prophet who prayed in a goat pen. This research is included in qualitative research using the method of ma'anil hadith. The methodology used in this research is library research with primary and secondary data sources. Data collection techniques used in this research are textual and contextual approaches. In analyzing the data, researchers used a descriptive-analytical approach. The result of this study is the Prophet's hadith of praying in a goat pen is an order. The delivery of the Hadith was motivated by the occurrence of the Khandak war at that time and the Prophet Muhammad at that time would pray and the Prophet also prayed in a goat pen. In addition, the situation at that time was that there were no buildings and mosques as a place of prayer.